Legalization of Waqf Forests in Indonesia: The Registration Process - Jannah, Miftahul; Sarkawi, Azila Ahmad; Othman, Jamilah (Indonesia Law Review, 2020)
Waqf (Islamic endowment) is considered one of the alternative solutions to environmental problems in Indonesia. One of the examples is through the establishment of a waqf forest, a conservation initiative in the form of developing forests on waqf land. The development of waqf forests needs to pay attention to the legal side in accordance with the laws and regulations of Indonesia. Previous studies discussed the process of legalizing waqf land in Indonesia, but research about the legalization of waqf forest land is still scarce. This study aims to determine the process of legalizing waqf forests on the basis of Indonesian laws and regulations. On the basis of the results of literature studies and expert interviews that were analyzed descriptively, the process of legalizing waqf forest is one of the main tasks of a nazir (waqf manager). The process involves at least three government agencies: the Ministry of Religion, the Ministry of Agrarian Affairs and Spatial Planning (National Land Agency), and the Ministry of Environment and Forestry. The waqf forest legalization process begins with making a waqf pledge deed at the local Office of Religious Affairs, followed by creating a waqf land certificate at the local Land Offices. A crucial step is to clarify that the represented land must be located outside the forest area through a statement from the Ministry of Environment and Forestry. The legalization of waqf forests will guarantee the sustainability of the forest because this process makes waqf forest legal under Islamic law and the law of the Republic of Indonesia.